Knowledge and practices of nurses regarding nosocomial infection control measures in private hospitals in Sana`a City, Yemen - Alrubaiee, Gamil; Baharom, Anisah; Kadir Shahar, Hayati; Mohd Daud, Shaffe; Omar Basaleem, Huda (BioMed Central, 2017)
Background: In the Yemeni healthcare setting, basic infection control measures are necessary to reduce the rates of hospital-associated infections. Methods: A descriptive cross-sectional study was conducted from April to May 2016. A non-probability sample of 100 nurses working in the private hospitals located in the capital city of Yemen was selected as study participants. A 45-item questionnaire was used to assess knowledge and practices regarding nosocomial infection control measures among the study subjects. The collected data were analyzed by SPSS (version 22.0). Results: The highest percentage of nurses were males (61.2%) and aging between 25 and above (71.8%) and had 3 years nursing diploma (60%), less than 5 years of employment in the hospitals (56.5%), relatively high training course about nosocomial infections (NIs) (64.7%), and working experience in infection control (78.8%). Most of the nurses (87%) had a fair level of knowledge, while only 4% of them had a good level of knowledge of preventive measures of nosocomial infections. The results also revealed that the majority of the nurses (71%) had fair practices about nosocomial infections whereas 26% of them had good practices and only 3% of them had poor practices. Conclusion: The gaps in knowledge and practices regarding NI control measures indicate the need to establish a related health care policy regarding NIs and implement a regular training program to upgrade and refresh the nurses’ knowledge and practices regarding NI control measures.